PEMBELAJARAN HUMANIZING THE CLASSROOM DENGAN PERKEMBANGAN EMOSI ANAK USIA DINI DI TK. DHARMA WANITA PROPPO KECAMATAN PROPPO KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021-2022 - Reza Ivon Nurcahya; Wahono Wahono; Naili Saâ€™ida (PROCEEDING UMSURABAYA, 2022)
The purpose of this study was to determine the Effect of Humanizing The Classroom Learning With Early Childhood Emotional Development in Kindergarten. Dharma Wanita Proppo, Proppo Subdistrict, Pamekasan Regency, 2021-2022 Academic Year. The teaching and learning process is a process that contains a series of actions of teachers and students on the basis of reciprocal relationships that take place in educational situations to achieve certain goals. The research method used in this study uses quantitative methods. With data collection techniques by observation, interviews, documentation. The results obtained in this study are the influence of Humanizing The Classroom learning with the emotional development of pre-school age children in Dharma Wanita Kindergarten Proppo, Proppo District, Pamekasan Regency for the 2021-2022 Academic Year. Humanizing the classroom approach in every classroom learning will stimulate the emotional intelligence of students in kindergarten. Dharma Wanita Proppo, because by humanizing the classroom, children don't get an outward and inner suppression, they don't do any coercion. Every problem that arises in the classroom for students, teachers are required to be more humaniz and identify the problem and look for the root of the problem and the solution can be solved.Â Keywords: Humanizing; educative; documentation; classroom